Autosomal dominant tubulointerstitial kidney disease: Diagnostic challenges in the absence of genetic testing. A case report - L. Surzhko; V. Nepomnyashchy (Український Журнал Нефрології та Діалізу, 2023)
Autosomal dominant tubulointerstitial kidney disease (ADTKD) is a group of rare uncommon genetic disorders characterized by tubular damage and interstitial fibrosis in the absence of glomerular lesions. It has autosomal dominant inheritance and inevitable progression to end-stage kidney disease (ESKD). In nephrological practice, we usually face glomerular diseases that have well-recognized symptoms. Therefore, when we see a patient with impaired kidney function but without any signs of glomerular disease, it is always more challenging to discover the reason for it. The present case illustrates tubulointerstitial lesions due to possible genetic reasons. A 38-year-old non-hypertensive female presented with impaired renal function, a family history of CKD, proteinuria 0,5 g/day, and urinary sediment unremarkable. Relying on her family history, the middle age of onset, the progression to the end-stage kidney disease, and laboratory and histological results, an autosomal dominant tubulointerstitial kidney disease was suspected. Initially, diagnosed tubulointerstitial kidney disease is likely to be secondary to a mutation in genes encoding mucin-1. Pathology findings in this case played a pivotal role in establishing the diagnosis. However, it still needs to be proven by genetic tests. The purpose of this manuscript was to summarize the case of ADTKD, discuss the challenges in diagnosing ADTKD without genetic testing, and emphasize the importance of genetic testing in confirming the diagnosis.